THE ANALYZE THE BUDDHADHAMMA PRINCIPLE WITH APPEARED IN THE BOAT SONG LAEM PHO, SONGKHLA PROVINCE. - ทิพย์ศรีนิมิ นิพนธ์; ธรรมานุกูล พระครูวินิจ; อุทัยวินัยกิจ พระครู; ธรรมประดิษฐ์ พระครูโสภณ (Journal of MCU Nakhondhat, 2015)
The objectives of this research were as follows 1. To study the background Boat Song Leam Pho in Songkhla province 2. To analyze the Buddha Dhamma principle which appeared in Boat Song Leam Pho in Songkhla province. And 3. To analyze the valuable of Buddha Dhamma of Boat Song Leam Pho in Songkhla province. This is the qualitative research, to collect the data from document and relavant researches with Boat Song Leam Pho in Songkhla province and the Dhamma doctrine from Buddhism and to have purposive interview by purposive sampling in coverage of Songkhla province. The research results found that: 1. Boat Song Leam Pho in Songkhla province which composed of Poetry (Klonpad) that the Buddhist lay who live in the area was compiled for singing in the Chakphra festival along the to play in the boat and then also play on the land but the symbol is the same is that paddle which can be seen as Boat Song. The Buddha Dhamma analytical results found that there are 4 level i.e. fundamental Dhamma, The medium Dhamma, high Dhamma, and Dhamma for daily life 3. The study of valuable of Boat Song Leam Pho in Songkhla province from the study found that there are six aspects as follows 1) The aspect of culture and tradition, 2) The aspect of Politics, 3) The aspect of economic, 4) The aspect of ethics 5. The aspect of entertainment 6. The aspect of environment.